PENGARUH LAYANAN BIMBINGAN KLASIKAL DENGAN TEKNIK SELF–MANAGEMENT TERHADAP PERILAKU TERLAMBAT SISWA KELAS IX IPS DI SMA NEGERI 1 STABAT - Desi Rahmawati; Nasrun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the ffect of classical guidance services using self-management techniques on student tardiness at Stabat 1 Public High School in the 2025/2026 academic year. This study is quantitative in nature with a pre-experimental design approach. The method used in this study is a one-group pretest-posttest design. The population in this study was all 11th grade social studies students at SMA Negeri 1 Stabat in the 2025/2026 academic year. Meanwhile, the sample in this study consisted of 33 12th grade social studies students. The results obtained in this study indicate that after the service was provided, there was an increase in disciplinary behavior, as evidenced by an increase in the number of students in the low category to 17 students (51.5%), while in the medium category there were 15 students (45.5%) and only 1 student (3%) in the high category. This means that after participating in classical guidance services using self-management techniques, the majority of students showed a decrease in tardiness behavior.